PECALANG SEGARA: SATUAN TUGAS KEAMANAN TRADISIONAL PENJAGA KELESTARIAN LINGKUNGAN PANTAI DAN LAUT: STUDI KASUS DI DESA PAKRAMAN PEMUTERAN, GROKGAK, BULELENG, BALI - Anantawikrama Tungga Atmadja (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractThis article is about background of founding pecalang segara (seashore security) and itsrole in preserving the beach and sea environment in Desa Pakraman Pemuteran, Grokgak,Buleleng, Bali. The disccusion of this problem is done through field research, usingqualitative approach that is based on critical social theory. Result of this research showsthat local community preserve their ocean because of ideology, ecology, economy, andsociology reason. The role of pecalang segara is very important, such restoration and coralcultivation, control and giving sanction toward crime on seashore and ocean ecosystem.This activity needs cooperation with any party, namely desa pakraman, desa dinas, hotelowner, local government, NGO, etc.